Application of a Molybdenum Carbide Electrode Enhanced the Biodegradability of Wheat Straw - Fang, Hao; Liu, YingHan; Qiu, Peng Xiang; Rajasekar, Adharsh; Song, Hai-Liang; Wang, Chu Qiao; Zhang, Shuai (Journal of electronic materials, 2022)
The disposal and management of wheat straw has become a major concern in wheat production countries because of its abundance. The potential of wheat straw as raw biomass could serve as a long-term sustainable resource if the lignocellulose polymer can be degraded efficiently. To break down this complex polymer and enhance the bioavailability of straw, we propose the application of stainless-steel-supported molybdenum carbide as the anode in electrochemical pretreatment. Our results indicate that the type of electrolyte used in electrolysis has a significant impact on the biodegradation efficiency of the polymer. Moreover, the data indicated that lignin was degraded by 7.4% in purified water and 6.2% in a NaOH system compared to the untreated group. The higher cellulose accessibility was confirmed by enzymatic hydrolysis in the NaOH system. The structural traits indicated that the bond energies of biomass lignocellulose were weakened to some extent in both purified water and NaOH systems. In addition, the enzymatic hydrolysis efficiency of straw treated by electrolysis with alkali electrolyte was significantly improved, and the yield of reducing sugar was increased by 17.9% and 116.8%, respectively, compared with those treated by NaOH alone and electrolysis, respectively. The results from our study also provide evidence that stainless-steel-supported molybdenum carbide along with an aqueous alkali (NaOH) can degrade the amorphous cellulose in lignocellulose and improve the bioavailability of straw effectively. Graphical Abstract